2007
DOI: 10.1080/09720073.2007.11891010
|View full text |Cite
|
Sign up to set email alerts
|

Biology of the Tribal Groups of Rajasthan, India: 4. Age Changes in Somatotype

Abstract: The present study is based on a cross-sectional investigation on 2928 samples consisting of 1503 males and 1425 females belonging to both adolescent (8 + to 18 + ) and adult age groups (19 & above). The study was carried out on the Scheduled Tribes, namely Mina, Bhil, Sahariya, Garasia, Damor and Kathodi of Rajasthan. Samples are collected from the place of residence and schools. The data for somatotype were collected following the internationally accepted standards. The calculated somatotypes are plotted on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Ashizawa et al [23] also found that, in the Philippine children from Manila, girls were signi�cantly taller than boys at ages 10 and 12 years in a well-off group, and at ages 11 and 12 in a low-income group, and heavier at age 12 in both groups. In consistent with the present study, with respect to height, boys of all tribal groups were taller than girls with few exceptions during preadolescent ages, and aer 14 years, boys became ultimately taller than girls [24]. Widiyani et al [25] also found out that body weight and height for both boys and girls accelerated with the advancement of age and similar to the present study, the sex differences existed signi�cantly aer 12 years of age.…”
Section: Discussionsupporting
confidence: 92%
“…Ashizawa et al [23] also found that, in the Philippine children from Manila, girls were signi�cantly taller than boys at ages 10 and 12 years in a well-off group, and at ages 11 and 12 in a low-income group, and heavier at age 12 in both groups. In consistent with the present study, with respect to height, boys of all tribal groups were taller than girls with few exceptions during preadolescent ages, and aer 14 years, boys became ultimately taller than girls [24]. Widiyani et al [25] also found out that body weight and height for both boys and girls accelerated with the advancement of age and similar to the present study, the sex differences existed signi�cantly aer 12 years of age.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, studies have also been conducted to find out the association of somatotype with arterial hypertension (Koleva et al 2002), abdominal adiposity (Williams et al 2000;Ramos-Jiménez et al 2019), blood pressure (Kalichman et al 2004), type 2 diabetes (Baltadjiev 2013;Urrutia-García et al 2015) etc. In India, the studies on somatotype are mostly on population variations in terms of age and sex variation -mainly conducted among children, adolescents and women (Gaur and Singh 1997;Gaur et al 1999;Gakhar and Malik 2002;Dkhar 2005;Bhasin and Jain 2007;Singh 2011;Srivastava et al 2012;Chandel and Malik 2012;Roy and Kundu Chowdhury 2013;Longkumer 2014;Kaur and Malik 2016;Kaur et al 2018;Chandel et al 2018;Mallick et al 2018;Shimrah et al 2020). However, such studies especially in adult tribal populations, are very few and far between (Ghosh and Malik 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Body physique is an individual phenomenon, which is influenced by multiple factors, such as age, sex, dietary pattern, ethnicity, and genetic and evolutionary factors (Bhasin & Jain, 2007; Chakrabarty et al, 2008; Ghosh et al, 2017; Kalichman & Kobliansky, 2006). It is also affected by the degree of environmental adaptation of a population (Chandel & Malik, 2012).…”
Section: Introductionmentioning
confidence: 99%